Developing New Treatments for Heart Failure: Focus on the Heart. (May 2016) - Gheorghiade, Mihai; Larson, Christopher J.; Shah, Sanjiv J.; Greene, Stephen J.; Cleland, John G.F.; Colucci, Wilson S.; Dunnmon, Preston; Epstein, Stephen E.; Kim, Raymond J.; Parsey, Ramin V.; Stockbridge, Norman; Carr, James; et al.
Abstract : Compared with heart failure (HF) care 20 to 30 years ago, there has been tremendous advancement in therapy for ambulatory HF with reduced ejection fraction with the use of agents that block maladaptive neurohormonal pathways. However, during the past decade, with few notable exceptions, the frequency of successful drug development programs has fallen as most novel therapies have failed to offer incremental benefit or raised safety concerns (ie, hypotension). Moreover, no therapy has been approved specifically for HF with preserved ejection fraction or for worsening chronic HF (including acutely decompensated HF). Across the spectrum of HF, preliminary results from many phase II trials have been promising but are frequently followed by unsuccessful phase III studies, highlighting a disconnect in the translational process between basic science discovery, early drug development, and definitive clinical testing in pivotal trials. A major unmet need in HF drug development is the ability to identify homogeneous subsets of patients whose underlying disease is driven by a specific mechanism that can be targeted using a new therapeutic agent. Drug development strategies should increasingly consider therapies that facilitate reverse remodeling by directly targeting the heart itself rather than strictly focusing on agents that unload the heart or target systemic neurohormones. Advancements in cardiac imaging may allow for more focused and direct assessment of drug effects on the heart early in the drug development process. To better understand and address the array of challenges facing current HF drug development, so that future efforts may have a better chance for success, the Food and Drug Administration facilitated a meeting on February 17, 2015, which was attended by clinicians, researchers, regulators, and industry representatives. The following discussion summarizes the key takeaway dialogue from this meeting.